Using Groupware for international collaborative learning - Clear, Tony; Daniels, M. (IEEE, 2000)
The paper reports the lessons learned from a two year collaborative learning trial between students at Auckland University of Technology (AUT) and Uppsala University. The trials took place using a combination of email and a custom developed Lotus NotesTM database. The first trial involved a case study in which students performed different roles in designing a software solution for an Auckland based nailcare distributor. The second trial built upon the knowledge base of the earlier trial, and required students to evaluate and rank the previous design proposals. A theoretical model developed from the group support systems literature guided some of the changes in the second trial. The software, the collaboration process and the evaluation methods evolved over the course of these trials. The challenges of creating global student communities within a short collaboration window in existing courses of study are discussed. Further extensions to this research are proposed and some general recommendations are made